Review and retrospective analysis of degenerative lumbosacral stenosis in 156 dogs treated by dorsal laminectomy - Suwankong, N.; Meij, B. P.; Voorhout, G.; de Boer, A. H.; Hazewinkel, H. A. W. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
The medical records of 156 dogs with degenerative lumbosacral stenosis (DLS) that underwent decompressive surgery were reviewed for signalment, history, clinical signs, imaging and surgical findings. The German Shepherd Dog (GSD) was most commonly affected (40/156, 25.6%). Pelvic limb lameness, caudal lumbar pain and pain evoked by lumbosacral pressure were the most frequent clinical findings. Radiography showed lumbosacral step formation in 78.8% (93/118) of the dogs which was associated with elongation of the sacral lamina in 18.6% (22/118). Compression of the cauda equina was diagnosed by imaging (epidurography, CT, or MRI) in 94.2% (147/156) of the dogs. Loss of the bright nucleus pulposus signal of the L7-S1 disc was found on T2-weighted MR images in 73.5% (25/34) of the dogs. The facet joint angle at L7-S1 was significantly smaller, and the tropism greater in GSD than in the other dog breeds. The smaller facet joint angle and higher incidence of tropism seen in the GSD may predispose this breed to DLS. Epidurography, CT, and MRI allow adequate visualization of cauda equina compression. During surgery, disc protrusion was found in 70.5% (110/156) of the dogs. Overall improvement after surgery was recorded in the medical records in 79.0% (83/105) of the dogs. Of the 38 owners that responded to questionnaires up to five years after surgery, 29 (76%) perceived an improvement.
Keywords: Degenerative lumbosacral stenosis; cauda equina; dog